Poverty and Inequality (London : C. W. Publishing Ltd.)
1944-10 1944 1940s 29 pages CONTENTS. PAGE INTRODUCTION 1 1. — INCOMES BELOW THE MINIMUM. (1) The Extent of Poverty 2 (2) Inadequate Earnings the Chief Cause of Poverty 3 (3) Poverty Thrice in a Lifetime 4 2. — INFERIOR EDUCATION. (1) The Class System of Education 5 (2) How Far do Scholarships break down the Divisions 6 (3) Waste of Ability 7 (4) Educational Background and the Best Jobs 8 (5) New Education Bill and its effects on Inequality......8 3. — MALNUTRITION. (1) The Standard of a Healthy Diet 9 (2) The Actual Diet of the Poor 9 (3) The Extent of Malnutrition 10 4. — ILL-HEALTH. (1) Infant Mortality 11 (2) Maternal Mortality 12 (3) Death Rate 12 (4) The Diseases of Poverty 13 5. — SLUMS AND OVERCROWDING. (1) Examples of Existing Slums 14 (2) Overcrowding To-day 14 (3) Why do these Conditions Persist 15 6. — CAPITALISM'S PALLIATIVES. (1) Public Assistance 16 (2) Unemployment Insurance 16 (3) Assistance Board 17 (4) Old Age, Women's and Orphan's Pensions 19 (5) National Health Insurance 20 (6) Workmen's Compensation 21 (7) War Pensions 22 7. — HOW POVERTY CAN BE ABOLISHED 23 8. — QUESTIONS FOR DISCUSSION 24 9. — READING LIST. 15X/2/98/13